The Significance of Bone Scintigraphy in the Evaluation of Metastatic Disease Before and After Therapy in a Patient with Prostate Cancer: a Case Report and a Review of Literature - Kotur, Milica; Grujičić, Lenka; Pantić, Nikola; Blagić, Miroslava; Šobić Šaranović, Dragana; Artiko, Vera (Medical Word, 2025)
Prostate cancer (PC) typically leads to osteoblastic metastases, primarily affecting the axial skeleton and subsequently the femur and humerus. We present a case in which the patient underwent bone scintigraphy (BS) following the diagnosis of PC—initially before the application of therapy due to suspicion of bone metastases and then a follow-up BS after therapy to evaluate treatment efficacy. A 69-year-old male patient underwent initial BS in October 2017. The scintigraphy results revealed multiple areas of asymmetrically increased radiopharmaceutical accumulation in the bones of the head, right clavicle, sternum, several ribs, the thoracic spine, all bones of the pelvis bilaterally, and the right femur. The BS conclusion indicated that the described lesions in the skeletal system were consistent with metastases originating from the previously diagnosed PC. In October 2021, the patient underwent a follow-up BS, after the applied therapy. Compared to the previous scintigraphic findings from 2017, the pathological process had shown complete regression within the skeletal system. No signs of bone metastases were detected. The presented case underscores the pivotal role of BS in detecting skeletal metastases and evaluating patients with confirmed metastases. The initial BS, in conjunction with other diagnostic methods, facilitated the selection of appropriate therapeutic modalities. Conversely, follow-up BS enabled the evaluation of treatment efficacy, and with a low prostate-specific antigen (PSA) level in the blood, the decision was made to discontinue therapy.
Keywords: prostate cancer; osteoblastic metastases; bone scintigraphy; androgen deprivation therapy